Connections in the Clinic Relational Narratives from Team-Based Primary Care - Reitz, Randall; Sudano, Laura E.; Knudson, Mark P. (Springer International Publishing : Imprint: Springer, 2021)
XXII, 295 p. 97 illus., 91 illus. in color.